Sociocultural Factors: Subsequent teenage Pregnancy life roject, Morelos, Mexico. 2012-2022 - Monterrubio-Flores, Eric Alejandro; León-Roger, Liliana; Rueda-Neria, Celina Magally; Parada-Toro, Irene M. (Horizonte Sanitario, 2024)
Objective: It consisted of describing the dynamics of subsequent teenage pregnancy in a municipality with urban and rural communities in the state of Morelos, and the conditions that influence the change in the mother’s life plan, through a qualitative perspective, the adolescent’s perception of dating stage, your first pregnancy, second pregnancy and your social environment in your life plan. Materials and methods: Cross-sectional study with multiple methods, the quantitative phase allowed us to analyze the trend and rates of teenage pregnancy, the qualitative phase consisted of the application of semi-structured interviews, previously prepared, emptied into a matrix for analysis, carried out from discourse analysis. A database was built in Microsoft Excel 365. Subsequently, with Stata v.14.2, univariate and bivariate analysis was performed to obtain mean, standard deviation, proportions with 95% confidence intervals. Results: They were grouped by ages of 17-20 years old (n=160) and 15-16 years old (n=5), the predominant education, primary 25.49% and secondary 52.94%. 87.18% work at home as housewives. 69.88% have had 2 pregnancies and 23.49% have had 3 pregnancies, 64.46% have had 2 births and 7.23% have had 3 or more births. 16.88% reported 2 cesarean sections, for the 17-20 years old group and 40% in the 15-17 years old group. 21.69% reported an abortion. The intergenic period was 12 to 24 months. The median age of the mothers was 19 years old with a minimum age of 15 and a maximum of 20 years. In the 17 to 20 years old group, the median was 19 years old and in the 15 to 16 years old group, the median was 16 years. Conclusions: Both the rate and prevalence of subsequent teenage pregnancies showed an irregular increase until 2019, before showing a decrease thereafter. Educational level is a determining factor for primary and subsequent teenage pregnancy.